The psychology of murder concealment acts - Mohammad Rahim Kamaluddin; Naji Arafat Mahat; Geshina Ayu Mat Saat; Azizah Othman; Ian Lloyd Anthony; Sowmya Kumar; Suzaily Wahab; Saravanan Meyappan; Balan Rathakrishnan; Fauziah Ibrahim (MDPI, 2021)
The escalating trend of murder victim concealment worldwide appears worrying, and literature does not reveal any specific study focusing on victim concealment amongst convicted male Malaysian murderers. Therefore, this study was aimed at investigating the psychological traits that may underlie the act of murder concealment in Malaysia via mixed method approaches. Male murderers (n = 71) from 11 prisons were selected via purposive sampling technique. In the quantitative analysis, a cross-sectional study design using the validated questionnaire was used. The questionnaire contained murder concealment variables and four Malay validated psychometric instruments measuring: personality traits, self-control, aggression, and cognitive distortion. The independent sample t-tests revealed the significantly higher level of anger in murderers who did not commit concealment acts (8.55 ± 2.85, p < 0.05) when compared with those who did so (6.40 ± 2.64). Meanwhile, the Kruskal–Wallis H test revealed that anger and the personality trait of aggressiveness hostility significantly varied across the different groups of murder concealment acts (p < 0.05). The qualitative data obtained via the in-depth interviews revealed two important themes for the murderers to commit murder concealment acts: (1) fear of discovery and punishment and (2) blaming others. These findings discussed from the perspectives of the murderers within the context of criminology and psychology may provide the first ever insight into the murder concealment acts in Malaysia that can benefit the relevant authorities for crime prevention and investigation efforts.